Relationships between stretch-shortening cycle performance and maximum muscle strength - Miyaguchi, K.; Demura, S. (The Journal of Strength and Conditioning Research, 2008)
This study aimed to examine the relationships between muscle power output using the stretch-shortening cycle (SSC) and maximum strength, as measured by the 1 RM (1 repetition maximum) test and the isokinetic dynamometer under elbow flexion. Sixteen trained, young adult males pulled a constant load of 40% MVC (maximum voluntary elbow flexion contraction) by ballistic elbow flexion under the following two preliminary conditions: 1) the static relaxed muscle state (SR condition) and 2) using the SSC (SSC condition). Muscle power was determined from the product of the pulling velocity and load mass by a power measurement instrument with a rotary encoder. The 1 RM bench press (1RM BP) and isokinetic maximum strength under elbow flexion with the Cybex-325 were measured as indicators of dynamic maximum strength. 1) The early power output exerted under the SSC condition showed a significant and high correlation with the 1 RM BP (r = 0.83), but only moderate correlation with the isokinetic muscle strength (r = 0.50-0.67). 2) The contribution of the 1 RM BP to the early muscle contraction velocity exerted under the SSC condition was large.